Deciphering Epithelial–Mesenchymal Transition Regulatory Networks in Cancer through Computational Approaches - Burger, Gerhard A.; Danen, Erik H. J.; Beltman, Joost B. (Frontiers in Oncology, 2017)
Epithelial-Mesenchymal Transition (EMT), the process by which epithelial cells can convert into motile mesenchymal cells, plays an important role in development and wound healing, but is also involved in cancer progression. It is increasingly recognized that EMT is a dynamic process involving multiple intermediate or 'hybrid' phenotypes, rather than an 'all-or-none' process. However, the role of EMT in various cancer hallmarks, including metastasis, is debated. Given the complexity of EMT regulation, computational modeling has proven to be an invaluable tool for cancer research, i.e., to resolve apparent conflicts in experimental data and to guide experiments by generating testable hypotheses. In this review, we provide an overview of computational modeling efforts that have been applied to regulation of EMT in the context of cancer progression and its associated tumor characteristics. Moreover, we identify possibilities to bridge different modeling approaches and point out outstanding questions in which computational modeling can contribute to advance our understanding of pathological EMT.